Effect of CO2 concentration on drought assessment in China. (26th April 2022) - Jiang, Huiyan; Wang, Guojie; Li, Shijie; Ullah, Waheed; Amankwah, Solomon Obiri Yeboah; Lu, Jiao
Abstract: Global climate change is projected to increase the probability of occurrence and severity of droughts. Increased CO2 concentration drives partial closure of plant stomata and reduces evapotranspiration. However, the impact of reduced evapotranspiration due to CO2 on future droughts characteristics in China is unclear. In this study, we have used the Coupled Model Intercomparison Project Phase 6 (CMIP6) global climate model simulations (GCMs) under historical period, and four shared socioeconomic pathway scenarios (SSP1‐2.6, SSP2‐4.5, SSP3‐7.0, and SSP5‐8.5) to estimate drought. We used a widely applicable drought index (i.e., the self‐calibrating Palmer Drought Severity Index [scPDSI]) to evaluate the historical and future drought conditions, using the Penman–Monteith formula with and without the CO2 concentrations. The results show that the increasing trend of scPDSI slows down when the CO2 effect is considered in all scenarios, especially in Heilongjiang, northern Xinjiang, and the Qinghai–Tibet Plateau. The divergence in the slowdown trend among the different scenarios becomes greater after 2030, with higher emission scenarios implying a greater slowdown in the increasing trend of scPDSI. After considering CO2, drought characteristics such as the drought frequency, intensity, and drought area decrease. Increased CO2 concentration on vegetation physiological processes could mitigate future drought. Therefore, the effects of CO2 on plant physiology should be considered in studies of future drought trends to develop more realistic response and adaptation policies to future drought changes. Abstract : Under the background of climate change and increasing human activities, considering CO2 in the drought index calculation gives a wetter assessment, and the gap is more pronounced in future scenarios. Different scenarios have similar spatial distributions, reflecting a significantly higher trend in these moisture‐limited areas of Heilongjiang, northern Xinjiang, and the Qinghai–Tibet Plateau. Therefore, it is necessary to take CO2 into account in drought assessments to give a more realistic representation of future drought conditions in China.